Political Component of Russian-Latvian Relations at the Present Stage (2014–early 2017) - Marat F. Kasem (Проблемы постсоветского пространства, 2017)
The article examines origins and causes of tensions in relations between Russia and Latvia today, their manifestations, and possible scenarios of their development in the future. The dominant feature of today’s Russian-Latvian relations is their political component. This situation first emerged in 2014, the year of the coup d’etat in Ukraine and the year of the Crimea joining Russia. The spirit of confrontation in Russian-Latvian relations and the increasing degree of tension has been fueled not by Russia but by Latvia, and, in the background of the situation, NATO, and, first and foremost, the United States. In 2005 the Latvian National Security Concept Program underscored “absence of military threat for Latvia or other Baltic states,” in 2015 the new edition changes its focus completely and mentions the “Russian threat.” Latvia does not play an independent role in foreign relations with Russia, but the country is using Russia as playing the role of an aggressor. As Latvia, Lithuania and Estonia are fully dependent on the US and the EU, they are forced to comply with foreign policy orders of their Western creditors, even if these demands contradict these countries’ own interests. Considerable changes have taken place in Latvia in the early 1917, when the legal status of US military personnel was changed.Consistently implementing these changes will turn virtually the entire territory of Latvia into the military infrastructure of the United States. As US military bases are being created in Latvia, it is equivalent of having American troops on the border with Russia. Obviously, Russia does not threaten Latvia in any way. An open conflict with NATO and the US could be used only as a last resort. But nothing depends on Moscow’s wishes anymore, and we can only watch the Baltic States being dragged further away from Russia. If previously, hoping to start a major European war, Washington placed its faith in Kyiv, now they find that strategy failing. The Baltic States appear to be an almost perfect testing ground for a major provocation. For now the Russian leadership still has some room for maneuver, but these options are rapidly shrinking. Almost all predictions about the future development of Russian-Latvian relations say that these will not be bilateral relations proper, but will depend on the dynamics of US-Russia relations. Looking at the dynamics of US military presence in Latvia, these predictions are fully justified.